2016
DOI: 10.1002/2015gl067545
|View full text |Cite
|
Sign up to set email alerts
|

Is the Brewer‐Dobson circulation increasing or moving upward?

Abstract: The meridional circulation of the stratosphere, or Brewer‐Dobson circulation (BDC), is projected to accelerate with increasing greenhouse gas (GHG) concentrations. The acceleration is typically quantified by changes in the tropical upward mass flux (Ftrop) across a given pressure surface. Simultaneously, models project a lifting of the entire atmospheric circulation in response to GHGs; notably, the tropopause rises about a kilometer over this century. In this study, it is shown that most of the BDC trend is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
68
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 38 publications
14
68
1
2
Order By: Relevance
“…The negative trend could indicate either an acceleration of the BDC (accompanied by related changes of isentropic mixing; see e.g. Ploeger et al, 2015a) or an additional upward shift of the circulation pattern as suggested by Oberländer-Hayn et al (2016). In any case, the strongest negative trend of about −0.25 yr decade −1 occurs in the northern tropics and is consistent with trends derived from model calculations (e.g.…”
Section: Discussionsupporting
confidence: 72%
“…The negative trend could indicate either an acceleration of the BDC (accompanied by related changes of isentropic mixing; see e.g. Ploeger et al, 2015a) or an additional upward shift of the circulation pattern as suggested by Oberländer-Hayn et al (2016). In any case, the strongest negative trend of about −0.25 yr decade −1 occurs in the northern tropics and is consistent with trends derived from model calculations (e.g.…”
Section: Discussionsupporting
confidence: 72%
“…This is in accordance with results from ECMWF reanalysis data for the past 2 decades (Wilcox et al, 2012). As indicated by Oberländer-Hayn et al (2016) regarding the BDC, the upward shift of the tropopause affects the interpretation of vertical profile differences between future and past. An air parcel which would have already entered the stratosphere under present-day conditions may be still considered tropospheric in the future.…”
Section: Implications Of a Rising Tropopause On Vsls Mixing Ratio Prosupporting
confidence: 78%
“…Chemical reactions are not computed interactively, e.g., via the EMAC submodel mecca (Sander et al, 2011a). The VSLS lifetime due to reaction with OH has been fixed to monthly mean values from the National Centre for Meteorological Research (CNRM) (Michou et al, 2011;Morgenstern et al, 2016) model calculations, while photolysis rates are computed within the EMAC submodel jval (Sander et al, 2014). Only in these simulations with simplified chemistry, OH concentrations have been set to zero in the lower troposphere (700-1000 hPa) to reduce the variability of ground level volume mixing ratio (VMR) of VSLS.…”
Section: Model and Experimentsmentioning
confidence: 99%
“…We evaluate the trends in the diabatic circulation from these three reanalysis data products and demonstrate that although there are trends in upwelling through pressure surfaces, the diabatic overturning through isentropes does not have the same clear trends. This result implies that much of the trend in the BDC might be attributable to changes in the thermal structure, supporting the conclusions of Oberländer-Hayn et al (2016). Finally, in this section we examine the upper and lower branches of the circulation in the diabatic circulation.…”
Section: Introductionsupporting
confidence: 49%
“…The mechanism for this increase in models involves the warming of the troposphere and cooling of the stratosphere strengthening the upper flank of the subtropical jets, causing the critical layers and Rossby wave drag to move upwards, allowing more Rossby wave activity in the lower stratosphere (Shepherd and McLandress, 2011; , 2011). It has also been suggested that this represents more of a "lifting" of the circulation as the height of the tropopause increases and that the mass circulation is largely unchanged (Oberländer-Hayn et al, 2016). Because the strength of the circulation is typically evaluated at a fixed pressure level, the rising tropopause height and associated rising circulation patterns would appear as an acceleration even if the total mass transport through the stratosphere were to remain unchanged.…”
Section: The Brewer-dobson Circulation Trends and Stratospheric Impmentioning
confidence: 99%